2019
DOI: 10.1186/s12883-019-1415-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum IL-36β and IL-36γ levels in patients with neuromyelitis optica spectrum disorders: association with disease activity

Abstract: Background Interleukin 36 (IL-36) cytokines belong to the IL-1 family and play an important role in some autoimmune diseases. However, the relationship between IL-36 and neuromyelitis optica spectrum disorders (NMOSD) remains unclear. Methods We determined serum IL-36α, IL-36β and IL-36γ levels and assessed correlations with clinical characteristics in 50 NMOSD patients and 30 healthy controls (HC). Results The concentrations of serum IL-36β … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In recent studies, serum IL-36 agonists levels were enhanced in NMOSD patients. This study proved that IL-36γ from neutrophils could stimulate microglia to produce neutrophil-stimulating cytokines, and may contribute to neuroinflammation by promoting neutrophil-recruitment ( Song et al, 2019 ; Yang et al, 2019 ) Neutrophils played an important role in the pathological mechanisms of NMOSD, because polymerization of abnormal neutrophils was found in NMOSD lesions, and the inhibition of neutrophilic protease could attenuate AQP4-IgG damage in the mouse brain ( Yang et al, 2019 ) In addition, murine bone-marrow derived dendritic cells (BMDC) and CD4 + T lymphocytes both expressed IL-36R and responded to IL-36α ( Song et al, 2019 ) In turn, the increase of IL-36α may affect immune cells in NMOSD and cause ongoing inflammation. There was a similar cytokine milieu in the cerebrospinal fluid of NMOSD patients and in the synovial fluid of patients with RA.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In recent studies, serum IL-36 agonists levels were enhanced in NMOSD patients. This study proved that IL-36γ from neutrophils could stimulate microglia to produce neutrophil-stimulating cytokines, and may contribute to neuroinflammation by promoting neutrophil-recruitment ( Song et al, 2019 ; Yang et al, 2019 ) Neutrophils played an important role in the pathological mechanisms of NMOSD, because polymerization of abnormal neutrophils was found in NMOSD lesions, and the inhibition of neutrophilic protease could attenuate AQP4-IgG damage in the mouse brain ( Yang et al, 2019 ) In addition, murine bone-marrow derived dendritic cells (BMDC) and CD4 + T lymphocytes both expressed IL-36R and responded to IL-36α ( Song et al, 2019 ) In turn, the increase of IL-36α may affect immune cells in NMOSD and cause ongoing inflammation. There was a similar cytokine milieu in the cerebrospinal fluid of NMOSD patients and in the synovial fluid of patients with RA.…”
Section: Introductionmentioning
confidence: 66%
“…There was a similar cytokine milieu in the cerebrospinal fluid of NMOSD patients and in the synovial fluid of patients with RA. Furthermore, IL-36α may locally ameliorate the effects of IL-17α and TNF-α, and contributed to the pathomechanisms of psoriasis ( Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of spinal lesions is correlated with inflammatory activity and neurological impairment (21,37) and is correlated with disease severity based on the admission EDSS score (38,39). Our study demonstrated for the first time that RGMa levels were positively correlated with the length of spinal lesions on NMOSD MRI scans.…”
Section: Discussionmentioning
confidence: 54%
“…Given the role of IL-36 in intestinal wound healing, it was suggested that this change in expression could result in persistent pro-inflammatory responses, leading to enterocolitis susceptibility in Hirschsprung’s disease affected infants [ 80 ]. IL-36 expression has also been observed to be altered in both myasthenia gravis and neuromyelitis optica spectrum disorder [ 81 , 82 ].These findings indicate that IL-36 may merit further investigation in brain and neurological diseases.…”
Section: The Role Of Il-36 In the Pathogenesis Of Inflammatory Diseasesmentioning
confidence: 99%